Comparison of different techniques to measure body composition in moderately active adolescents. Issue 3 (September 1998) - De Lorenzo, A; Bertini, I; Candeloro, N; Iacopino, L; Andreoli, A; Van Loan, M D
Abstract : OBJECTIVE: To evaluate the differences in the estimate of body fat percentage (%FM) and the amount (kg) of fat free mass (FFM) by different methods in 26 moderately active adolescents very similar in age, body fatness, and training status. METHODS: Mean (SD) age was 16.7 (0.9) years, height was 177.0 (5.1) cm, and weight 68.0 (5.2) kg. %FM was assessed using dual-energy x ray absorptiometry (DXA) and two skinfold prediction equations: that of Slaughter et al (%FM Sla) and that of Deurenberg et al (%FM Deu). In the same way, FFM was measured using DXA and different impedance equations: those of Suprasongsin et al (FFM Sup), Schaefer et al (FFM Sch), Houtkooper et al (FFM Hou), and Deurenberg et al (FFM Deu). To determine the interchangeability of the different methods of measuring %FM and FFM, one way analysis of variance, standard error (SE), and coefficient of variation (CV%) ((SD/mean) x 100) were used. RESULTS: On average, no significant statistical differences were observed between the values determined for %FM: DXA value, 11.7 (5.4%); %FM Sla, 10.9 (4.0)%; %FM Deu, 11.5 (2.3)%. On the other hand, SE and CV% between each pair of the three methods used showed very large variability. With regard to the measurement or prediction of FFM, the mean value measured by DXA was significantly higher than that predicted by the equation of Sch (+7.2 kg, p < 0.001), Deu (+3.2 kg, p < 0.001), and Hou (+2.6 kg, p < 0.001), whereas it was lower than that predicted by the equation of Sup (-1.6 kg, p < 0.05). The Hou and Deu values were the only two that, on average, did not differ in a statistically significant way, although they showed the highest CV%. CONCLUSIONS: In our sample of moderately active adolescents the estimated values for %FM and FFM appear to be highly dependent on method.